The creation of jobs and productive units of the Creative Economy in the Region of Corede Vale do Rio dos Sinos - CONSINOS - RS / Brazil from 1996 to 2009. New Perspective Development - Judite Bem; Nelci Maria Richter Giacomini; Gislaine Cristina de Souza Rech (European Regional Science Association (ERSA), 2011)
Activities that develop in a region, using resources to be produced and generating results that affect the economy and trigger a multiplier effect on employment and income. The activities on the economy of culture have this effect on the economy, namely the impact that investments generate benefits they bring on other productive activities. The United Nations Conference on Trade and Development (UNCTAD) - UN Special Body was established in 1964 as a result of demands from countries with lower levels of development, aiming to establish a permanent international court which would be based approach to development. This has pursued the implications of the importance of activities from creative industries, cultural activities linked to a region and argues that the value generated by them is able to turn them economically as their commercial value is transferred to different areas of economic a region. From this perspective, the creative industries are large group activities can boost a city economically; therefore they are highly creative ability of the population of this region. The Corede Vale do Rio dos Sinos - CONSINOS - is a region politically instituted in the early-1990s, the State Government of RS and aims to formulate and implement regional strategies, consolidating them into regional strategic development plans. It consists of 14 municipalities, with industrial production is strongly focused on five cities: Campo Bom Canoas, Novo Hamburgo, S\~Ao Leopoldo and Sapucaia. Economically, it presents a strong dependence on the leather-footwear industry and its components which have resulted in a dynamic problem for the region, because it undergoes large swings forward exchange rate issues and export entry of Chinese products, among others. The objective is to define what is meant by creative industries and verify by the number of jobs and production units, whether the region can develop in the medium term other activities that may replace the dependence of the footwear sector and, therefore, make other possibilities in the production matrix.
Keywords: 330; Employment; Creative Economy; Creative Industries; Consinos